The Meritorious Learning Rewards Promoted by Chat GPT in Academic Writing Classroom Contexts - Kristian Wijaya; Adeseko Sunday Olaifa; Moses Adeleke Adeoye (Educalingua, 2024)
One of the most conspicuous and serious hindrances oftentimes confronted in these presently-situated academic writing learning dynamics is the constant presence of an emotionally-exhausting and anxiety-inducing learning environment in which EFL learners experience the absence of writing enjoyment. To better lessen this debilitating hurdle, second language educators are highly recommended to start activating the proper usage of artificial intelligence platforms in their regular academic writing learning enterprises. By carrying out this initiative, EFL learners will be mentally constructed upon facing the possible occurrence of taxing academic writing learning obstructions. This small-scale library investigation was initiated by the researcher to profoundly explore the potential meritorious learning rewards promoted by ChatGPT in modern academic writing classroom contexts. To achieve this major study objective, the researcher made use of a thematic analysis approach in analyzing the identical research results yielded by 20 previously-published ChatGPT scientific journals. The main purpose of embedding this research methodology is to ascertain the relevancy, applicability, and robustness of impendent research outcomes. Two major reasons underlined worldwide second language educationalists to internalize the ChatGPT tool at the onset of variegated academic writing classroom settings namely the significant reduction of writing errors and the realization of proficient academic writers.